Virgin olive oil : production, composition, uses and benefits for man - Leonardis, Antonella de (Food and beverage consumption and health series., 2014)
Olive oil is considered to be such a crucial component of the so-called 'Mediterranean Diet' that, since 2010, it has been inscribed in UNESCO's list of Intangible Cultural Heritage of Humanity, and is considered to be a very good dietary habit. In addition, a copious amount of scientific literature has provided evidence that regular consumption of olive oil is associated with longevity, healthier aging, cardiovascular health, prevention and protection against cancer. Currently, olive oil is gaining a worldwide rise in popularity given that it is widely considered to be a functional food able.